MEMBUMIHANGUSKAN MOJOAGUNG: KONDISI MOJOAGUNG 1945-1949 - Santoso, Alfian Widi (Program Studi Sejarah Peradaban Islam Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2022)
Mojoagung is a sub-district located on the eastern outskirts of Jombang district which is also directly adjacent to Mojokerto district. Mojoagung itself has a very long history, because Mojoagung itself is a very strategic area, because it is crossed by roads between provinces. With its strategic position, Mojoagung eventually occupied several historical stages from the Islamic Mataram period to the post-independence period. Therefore, this writing aims to discuss something that is quite interesting and very related to today, namely